Evaluation of health, safety and welfare promotion at workplace: AreviewofNestle India Ltd. [A Factor Analysis Approach] - Bhatia, Raminder Kaur; Sidhu, Shubpreet; Kaur, Baljinder (Gyan Management Journal, 2010)
Working conditions have attracted a great deal o attention of managements of business and ot!-:, · organizations in the recent years. There are two basic reasons for this .Firstly, the growth rate of trc:, union movement has compelled the managements to provide better working conditions to :
Keywords: Health; safety; efficiency; Nestle India Ltd